Biosynthesis of Silver Nanoparticles Using Aegle marmelos (Bael) Fruit Extract and Its Application to Prevent Adhesion of Bacteria: A Strategy to Control Microfouling - A. Nithya Deva Krupa; Vimala Raghavan (Bioinorganic Chemistry and Applications)
Marine biofilms formed due to adhesion of bacteria and other microorganisms on submerged surfaces are generally considered to be a major form of microfouling. Subsequent attachment of larvae of higher organisms like barnacles, mussels, and so forth, on marine biofilms, causes macrofouling. Several approaches have been used to prevent micro- and macrofouling. Silver nanoparticles (AgNPs) are known to exhibit strong inhibitory and antimicrobial activity. Biological synthesis of AgNPs is rapidly gaining importance due to its growing success. Hence, the present study is focused on the biosynthesis of AgNPs using fruit extract of Aegle marmelos and its characterization through UV-Vis spectrophotometer, X-ray diffractometer (XRD), Fourier transform infrared spectroscopy (FTIR), and atomic force microscopy (AFM). Further isolation and identification of marine biofilm forming bacteria were carried out through 16S rDNA analysis. The antimicrofouling effect of the biosynthesized AgNPs was tested against marine biofilm forming bacteria and the results suggested that it could effectively inhibit biofilm formation. This preliminary study has proved that AgNPs may be used as antimicrofouling agent for the prevention of biofouling in the early stages.